Pemberdayaan Masyarakat Melalui Potensi Sumber Daya Lokal Melalui Peningkatan Kualitas Pengelolaan Garam Desa Sidomukti - Siswadi, Siswadi; Zaini, Ahmad Afan; Kaswari, Anggi; Rohman, Ah. Taufiqur; Febriliya, Anggun; Romadhoni, Putri Amalia (Universitas Sunan Drajat Lamongan, Indonesia, 2025)
Sidomukti Village, located in Bondong District, Lamongan Regency, is a tropical area with significant agricultural potential. One of the dominant types of agriculture in this village is salt farming. However, the salt harvest season often experiences price fluctuations due to changes in weather and variations in the quality of salt produced. This community service program aimed to address this issue by improving the quality of salt production. The research utilized the Participatory Action Research (PAR) method, with data collected through interviews with local salt farmers. The seminar program conducted had three main objectives: (1) to increase the community's knowledge of producing high-quality salt, (2) to develop innovative community-based practices, and (3) to enhance the quality of local village resources. The program was carried out in three phases: preparation, implementation, and evaluation. The results of the seminar activities showed an increase in public awareness and knowledge related to quality salt production, which is expected to improve the selling value of the salt.